Growing Public Concern Towards the Implementation of Inclusive Education - Rifqi Khairul Anam (PT. Pusmedia Group Indonesia, 2024)
There are children in this world who have special needs and experience significant abnormalities or deviations in their physical, mental, intellectual, social, and emotional development compared to other children of the same age. As a result, they require special education services. Inclusive education is a specialized kind of education designed to cater to the unique requirements of children with special needs. The underlying principle of this educational concept is to shift the focus from adapting students to fit the requirements of the school, to instead adapting schools or educational systems to accommodate the needs of children. Researchers did community service by socializing education for children with special needs at the ABA 5 Probolinggo Kindergarten inclusive school. The focus of the community service was